Methodological Aspects of Pedagogy's Two-Discipline Location - Danuta Urbaniak - Zając (Nicolaus Copernicus University in Toruń, 2020)
The area of pedagogy research penetration is situated in the disciplines of social sciences and humanities. The answer to the question what methodological consequences this brings to the practice of pedagogy favours the broadening of the ethodological awareness of pedagogues. The author adopts a conventional starting point, established by W. Dilthey's statement that some sciences explain the world and other understand it, in which the research practice of social sciences, which adapted the method of natural sciences, was diametrically different from the research in the humanities. This difference is expressed, among other things, in the different treatment of the method, as well as the different position of the researcher in the research process. Nowadays the methodology of social sciences is internally diverse. There is a current within it, referred to as qualitative research, in which the influence of achievements in the field of humanities is clearly visible, and which becomes a source of premises for the recognition of reality in empirical cognition